2019
DOI: 10.21101/cejph.a5140
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between physical activity, dietary intake and bone parameters in 10-12 years old Hungarian boys and girls

Abstract: Objectives: Physical activity (PA) and adequate macro-and micronutrient intake have favourable influence on the bone status. The aim of this study was to analyse the relationships among PA, anthropometric data, dietary intake and ultrasound bone characteristics in children.Methods: 10-12 years old Hungarian children (N = 123, 59 girls, 64 boys) provided physical activity, diet, anthropometric and bone data. PA was measured with accelerometer (Actigraph GT3X+). Diet was evaluated with three-day, 24-hour food re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Only 9/30 studies [39,41,53,54,58,[61][62][63][64] had a 'yes' response to item 9, where participants were required to have ≥ 4 days with ≥ 10 h of accelerometer data. Despite satisfying this requirement, four of these studies [58,[61][62][63] were still deemed to be of poor quality as they had not controlled for important covariates (e.g. age, sex, ethnicity, maturational stage, skeletal/body size) in the analyses when investigating independent associations between bone outcomes and each activity intensity (MPA and/or MVPA and VPA).…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 9/30 studies [39,41,53,54,58,[61][62][63][64] had a 'yes' response to item 9, where participants were required to have ≥ 4 days with ≥ 10 h of accelerometer data. Despite satisfying this requirement, four of these studies [58,[61][62][63] were still deemed to be of poor quality as they had not controlled for important covariates (e.g. age, sex, ethnicity, maturational stage, skeletal/body size) in the analyses when investigating independent associations between bone outcomes and each activity intensity (MPA and/or MVPA and VPA).…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
“…Of the eleven studies assessing outcomes at this site, one did not report significant associations (including at the superlateral and inferomedial subregions) [64]. Significant, positive associations were reported 3 impact bands (low, medium and high) 1 (3) [46] 6 impact bands (from brisk walking to jumping) 1 (3) [45] Accelerometer make and model † Actigraph GT1M 14 (47) [24,41,43,44,47,49,52,56,59,[63][64][65][66][67] MTI 7164 6 (20) [24,48,50,60,61,65] Actigraph GT3X 3 (10) [44,56,66] Actigraph GT3X + 3 (10) [53,54,58] Actigraph Actitrainer 3 (10) [44,49,56] WAM 6471 2 (7) [42,55] Newtest monitor 2 (7) [45,46] Actiwatch motion sensor 1 (3) [57] Actigraph wGT3X-BT 1 (3) [51] Actical 1 (3) [39] Lifecorder GS 1 (3) [62] GENEActiv 1 (3) [40] Wear location Right hip 18 (60) [24, 39, 41-44, 49, 51-53, 55, 56, 60, 61, 63, 64, 66, 67] Lumbar spine/lower back 3 (10) [47,…”
Section: Dxa: All Sitesmentioning
confidence: 99%
“…Our results show that the incidence of osteopenia in CPT group is higher than that in the control group, and the SOS, STI, QUI, and BMDe of CPT children are lower than those of non-bone metabolic disease children. SOS is an index to evaluate the bone quality and strength, which is proportional to bone mass and can better predict the risk of fracture [22]. Therefore, our results suggesting that the bone mass of children with CPT may be lower than the controls, and could be more prone to fracture.…”
Section: Discussionmentioning
confidence: 70%
“…Physical activity and adequate nutrient intake have favorable influence on the bone quality. Hungarian researchers demonstrated that changes in bone mineral status among 10–12-year-old children, assessed by ultrasound method, are correlated with the amount of intense physical activity as well as with optimal vitamin K intake [ 32 ].…”
Section: The Importance Of Vitamin K2 Supplementation In Various Pathological Conditionsmentioning
confidence: 99%